RELATIONSHIP BETWEEN THE PERCEPTIONS OF EFFORT HYPERTROPHY TRAINING (Fiep Bulletin - online, 2016)
The objective of this study was to analyze the perception of effort in relation to the goal of hypertrophy training. 50 male individuals were selected practitioners in hypertrophy training, an average of 25.14 ± 5.9 years and at least six months of practice. The exercises were bench press and leg press 45 °. We used scale exertion and submaximal test of strength. The results show that the bench press was no difference (p
Keywords: Intensity; Hypertrophy Training; Stress Perception Scale